Fatty acids and terpenoids from Canarium odontophyllum Miq. leaf and their antioxidant and cytotoxic effects on UVB-induced immortalized human keratinocytes cells (HaCat) - Muhammad Wahizul Haswan Abdul Aziz,; Dayang Fredalina Basri,; Siti Fathiah Masre,; Ahmad Rohi Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study evaluated the antioxidant capacity of hexane extract of Canarium odontophyllum Miq. leaf; its fatty acids and terpenoids content; and cytotoxic effects on UVB-induced human keratinocytes (HaCaT). FRAP assay was used to determine antioxidant capacity. GC-MS analysis to identify the fatty acids and terpenoids’ in the hexane extract of Canarium odontophyllum Miq. leaf. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was carried out to measure the cytotoxic effects of the extract on UVB-induced human keratinocytes. Serial doses of up to 1000 μg/mL extract were administered before UVB irradiation of the cells. FRAP assay showed the extract was found to exhibit antioxidant activity but no significant difference in ascorbic acid equivalent antioxidant capacity (AEAC) between dose 500 μg/mL (5.00 ± 0.35 AEAC) and 1000 μg/mL (5.70 ± 0.29 AEAC) extract. GC-MS analysis showed the extract contained 88.93% of fatty acids and terpenoids, especially n-hexadecanoic acid, spathulenol, and phytol. MTT assay showed no IC50 value for the tested extract dose on UVB-induced HaCaT. Thus, the results suggest the potential application of hexane extract of C. odontophyllum Miq. leaf in terpenoids’ studies. In-depth research and isolation of compounds of interest should be done to develop it as a viable medical phytotherapeutic agent.